The Development of Virtual Training Environment for Computer Parts Installation Process - Maizatul Akmal, Yahaya (2009)
Virtual Reality-based training system (VRTS) is an advanced computer-assisted training system using Virtual Reality (VR) technology. VR is a computer generated environment which gives the illusion of three dimensions. It provides a true 3D interface to a range of computer applications. The essence of virtual reality is immersion, which is the ability to immerse the computer user in a computer generated experience. In this project, I proposed the video based interaction in the distributed virtual training environment. To make the interaction possible, I will develop a video based using 3D software to guide customer for parts installation. The use of 3D of 3D virtual training will allow the organization to help customers to install parts in the computer will be easier and cost saving. The proposed video will allow cost efficient video based interaction, and the discussion regarding the advantages of virtual training , limitations and possible future research on the video based interactions in the virtual environment.